The Relationship Between Financial Ratios, Company Growth, and Shareholder Value in Financial Statement Reporting - Wiryamanta, Rafif Putra; Kurnia, Silvi; Hamada, Maurheen Queena; Nugraha, Viery Erlangga; Pandin, Maria Yovita R (International Publisher, 2025)
This study examines the relationship between corporate expansion, crucial financial indicators, and the worth attributed to shareholders, specifically within companies listed on the Indonesia Stock Exchange. The financial metrics considered in this analysis are Return on Equity (ROE), the Debt to Equity Ratio (DER), and Earnings Per Share (EPS). A quantitative approach was adopted, involving the examination of financial statements spanning from 2018 to 2022. Multiple regression analysis was utilized to assess how independent variables affect shareholder value. The findings indicate that both ROE and company growth positively influence shareholder value, whereas a higher DER negatively impacts it. These results highlight the critical role of proficient management in optimizing equity utilization and managing debt to enhance company valuation. This study contributes to a deeper understanding of how financial ratios and growth interact to shape shareholder value. It offers recommendations for company leadership to prioritize boosting ROE and fostering sustainable growth while mitigating debt-related risks. Furthermore, it suggests that future studies could benefit from a broader sample and the inclusion of macroeconomic factors for more robust conclusions. Consequently, this research can inform sound investment choices and financial management approaches for businesses.